2019
DOI: 10.1002/ece3.5811
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phlebotomine sand flies (Diptera: Psychodidae) from leishmaniasis endemic areas in southeastern Mexico using DNA barcoding

Abstract: Leishmaniasis, a vector‐borne disease transmitted to humans through the bite of phlebotomine sand flies, is of public health significance in southeastern Mexico. Active and continuous monitoring of vectors is an important aspect of disease control for the prediction of potential outbreaks. Thus, the correct identification of vectors is paramount in this regard. In this study, we employed DNA barcoding as a tool for identifying phlebotomine sand flies collected in localized cutaneous leishmaniasis endemic areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…For Psychodidae, the distances ranged from 0– 4.9% within the family in Brazil, and increased to 0– 8.32% when including multiple countries in the Neotropical region (de Souza Pinto et al, 2022, Posada-Lopez et al, 2023). When focusing only on Mexico, Adeniran et al (2019) found intraspecific distances of 0.12–1.22%. This range increased to 0–9.48% when including other sequences from North and South America (Adeniran et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For Psychodidae, the distances ranged from 0– 4.9% within the family in Brazil, and increased to 0– 8.32% when including multiple countries in the Neotropical region (de Souza Pinto et al, 2022, Posada-Lopez et al, 2023). When focusing only on Mexico, Adeniran et al (2019) found intraspecific distances of 0.12–1.22%. This range increased to 0–9.48% when including other sequences from North and South America (Adeniran et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…When focusing only on Mexico, Adeniran et al (2019) found intraspecific distances of 0.12–1.22%. This range increased to 0–9.48% when including other sequences from North and South America (Adeniran et al, 2019). The maximum intraspecific distance was 1.07% for Psychodidae in our study, which is similar to other studies that focused on small geographic regions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The 658-bp DNA barcode region of the cytochrome c oxidase subunit 1 (COI) was ampli ed using the invertebrate-speci c primers LCO1490 (5'-GGTCAACAAATCATAAAGATATTGG-3') and HCO2198 (5'-TAAACTTCAGGGTGACCAAAAAATCA-3') (22,23). PCR reactions were performed in an Eppendorf Mastercycler Gradient 5331 (Eppendorf, USA) with a total volume of 20 µl, including 3 µl of DNA extract, 1X of Platinum II Hot Start Master Mix (Invitrogen, Thermo Fisher Scienti c), 0.2 µM of each primer, and nuclease-free water.…”
Section: Sand Y Morphological and Molecular Identi Cationmentioning
confidence: 99%
“…DNA barcoding is an effective tool for molecular identification of insects, especially grasshoppers (Cywinska et al 2006). The fundamental purpose of DNA barcoding is to standardize molecular methods for complementary morphological species identification (Azpurua et al 2010, Gutierrez et al 2014, Adeniran et al 2019. Six grasshopper species were identified that were collected from different paddy fields.…”
Section: Interspecific Genetic Distancementioning
confidence: 99%